Bio-applications and biotechnological applications of nanodiamonds - Muhammad Bilal (Elsevier, 2021)
The recent advancement in the nanotechnological sector has evidently revolutionized the biotech- and biomed-divisions of the twenty-first century. Accordingly, designing and fabrication of robust materials, for instance nanodiamonds (NDs), at the micro- and nano-scale with unique structural, physiochemical, and functional features have been the focus of technological investment and are becoming popular in different areas of science. Particularly, NDs among various nanomaterials are of supreme interest with significant market value due to their unique structural fabrication, ease in surface modification, minimal/no toxicity, biocompatibility, facile biodegradation and/or safer exit upon administration safety, patient compliance, and smart action. Therefore, the interest to deploy NDs in many applications is on the rise over the past few years. Though a plethora of literature is available on the NDs, but in a scattered manner. Thus, this work is an effort to spotlight the detailed surface chemistry and comprehensive coverage of biotech- and biomed-applications of NDs, at a single venue. Considering the above critics, herein, we reviewed state-of-the-art NDs as a smart and sophisticated platform – namely as a nanotechnological strategy to construct and deploy high-end products to withstand the biotechnological and biomedical sectors of the modern world. Following a brief introductory statement of problems and opportunities, structural and functional entities of NDs with reference to their surface chemistry are given with examples. The latter half is focused on the NDs applications in catalysis, sensing, separation, drug delivery, gene delivery, and cosmeceutical formulations. Finally, an overview is also given on the NDs-assisted products in the market, along with research gaps and future trends in NDs research are also included in this review.